2023
DOI: 10.1007/s43032-023-01252-6
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Techniques and Risk of Congenital Heart Diseases in Children: a Systematic Review and Meta-analysis

Abstract: Infertility is a growing phenomenon and leads to an increased use of assisted reproductive techniques (ARTs). In recent years, concerns about the safety of these procedures emerged and ARTs were hypothesized to be a risk factor for developing congenital heart diseases (CHDs) in offspring. Our aim is to investigate the association between ART and CHD, specifying results according to various subtypes of defects. We performed a systematic review and random-effects meta-analysis following the PRISMA guidelines. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Up to now, the causes of CHD remain mainly unclear, but increasing the environmental factors apart from genetic background 29 . In our study, during the variable selection process, we found that early-pregnancy BMI 30 , gravidity, assisted reproduction 31 , medication history 32 , passive smoking 33 , exposure to air environmental pollution 34 were associated with CHD risk in offspring, which were also proved to play important roles in CHD development in prior study. Thus, we adjusted those factors to explore the independent impact of lipid profile on offspring CHD in early pregnancy.…”
Section: Discussionmentioning
confidence: 49%
“…Up to now, the causes of CHD remain mainly unclear, but increasing the environmental factors apart from genetic background 29 . In our study, during the variable selection process, we found that early-pregnancy BMI 30 , gravidity, assisted reproduction 31 , medication history 32 , passive smoking 33 , exposure to air environmental pollution 34 were associated with CHD risk in offspring, which were also proved to play important roles in CHD development in prior study. Thus, we adjusted those factors to explore the independent impact of lipid profile on offspring CHD in early pregnancy.…”
Section: Discussionmentioning
confidence: 49%
“…Eight studies with a sample size of 6,108 were included in the final analysis, and the sample sizes of the individual studies ranged from 86 to 2007 [ 19 , 22 ]. The range of positive attitudes toward embryo acceptance was reported from 10% in Japan [ 13 ] to 94% in Spain [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study analyzing 24 studies found a 3% pooled incidence of congenital heart disease in ART pregnancies, with a 1% decrease for major CHDs. ART pregnancies have an increased risk of minor CHDs, but insufficient evidence for major CHDs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ART is a risk factor for some CHD, in addition to individual risk factors of the pregnant woman. Many women accessing ART have factors such as age and race that proportionally increase the risk of CHD (20,21). Preimplantation diagnosis for congenital anomalies, including CHD and DGS, is conducted individually, taking into account pathological history with Mendelian inheritance patterns, advanced maternal age, family history of genetic syndromes, among others.…”
Section: Discussionmentioning
confidence: 99%